Electronic module protist material based on ASICC learning strategies - Qonita Nur Rohmania; Inayah Nur Afifah; F. Fatnatin; Poppy Rahmatika Primandiri; Mumun Nurmilawati; Agus Muji Santoso (Universitas Muhammadiyah Malang, 2022)
The process of scientific argumentation skills in biology learning at SMAN 1 Kediri is nonoptimal yet. This study aimed at improving students’ scientific argumentation using ASICC-based electronic modules. This Research and Development employed Plomp development model. The subjects of this study were X graders of MIPA SMAN 1 Kediri which consisted of 32 students. There were three stages of the Plomp model conducted i.e., preliminary research, prototyping, and assessment. The expert validation score gained for subject matter and linguistic was 85% (valid category), the validation score for design and media professionals' validation is 81% with a valid category, the teacher validation score is 93% with a very valid category, and the small group test score is 88% with a very valid category. Implementation of the ASICC-based electronic module had results such as 25 of 32 students got the N-Gain score in the high category, 5 students in the medium category, and 2 students in the low category. The ASICC-based electronic module on protist material is valid and effective to improve the scientific argumentation skills of class X MIPA students in SMAN 1 Kediri.